Development Of Wireless Sensor Network For Monitoring Indoor Air Quality - Idris, Mohaiyedin (2010)
It is an undeniable fact that air quality is vital in our daily lives. The contributing indoor air pollution at the workplace or in our residential areas has caught the attention of scientists and generally, the public in recent years. It is interesting to find that the studies done came up with the discovery that the indoor air pollution contributes higher degree of air contaminants compared to the level of air pollution outdoor. This is probably explained by the fact that people tend to spend 90 % of their time indoor and the rest on outdoor activities. Unpolluted air furnishes us with good, comfortable, and healthy lifestyles which may lead to a productive working environment and at the same time, contribute to a better peace of mind. The approach of wireless sensor network is applied in order to detect and monitor the indoor air pollution. The air quality parameters such as air temperature, percentage of relative humidity, and air contaminants are carried out in this research. LM35DZ temperature sensor and A0545 humidity sensor are employed to measure air temperature and relative humidity in percentage. Based on these two measurements, dew point is obtained to measure the level of air temperature required to produce 100 % relative humidity. The TGS2600 semiconductor gas sensor is employed to detect air contaminants of carbon monoxide with 0.0188 mean square error. In this research, six nodes and a data handler are developed. Each sensor node consists of PIC16F877 microcontroller device with three sensors (temperature, humidity and gas sensors) and SRWF-508 transceiver module. All the sensor nodes are connected to the data handler through the star network to monitor air quality.